PROPERTIES OF NANOSTRUCTURED MATERIALS ASSISTED BY CAPILLARYCELL METHOD - Ye. T. Taurbayev; Z. Zh. Zhanabayev; V. Yu. Timoshenko (Вестник. Серия физическая, 2009)
Wafers of silicon and compound semiconductors were treated in a capillary-cell by using electrochemical or chemical etching (stain etching). Atomic force microscopy, infrared spectroscopy and Raman scattering methods revealed nanoporous and nanocrystalline structure of the treated surfaces. The formed porous semiconductors demonstrated efficient photoluminescence, which could be controlled by etching parameters, i.e. current density, electrolyte content, etc. These results indicate good prospects of the employed capillary-cell method for preparing nanostructured porous materials with desired structure and optical properties.